Forced Marriage: Implementation of the Mandatory Provisions of the Bride’s Consent in Indonesia - Syahrul Mubarak Subeitan (Institut Agama Islam Negeri Batusangkar, 2022)
This paper aims to explain the relevance of the text (naṣ) and the provisions on how the rules for the consent of the bride and groom must be met with the problem of forced marriage in Indonesia. This paper is a qualitative research with a juridical-normative approach which is analyzed using a thematic-holistic method. The results show that the support of the two prospective brides is absolute in marriage, although in Islamic law, there are schools of thought that state the right of ijbar wali (forced marriage). Based on this, the meaning of marriage can be achieved with the following indicators: First, there is pleasure between the bride and groom, and they have known each other and agreed to carry out the marriage so that the marriage can be carried out safely and peacefully; Second, it can avoid acts of domestic violence due to marriages that do not have the pleasure of the bride and groom; Third, prioritizing willingness to achieve the purpose of marriage; and Fourth, obedience to God based on Islamic teachings. These indicators expect to overcome the problem of forced marriage so that a family is sakinah, mawaddah, warahmah.